2002
DOI: 10.1080/014436121000020484
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal sacrospinous fixation: experience in a district general hospital

Abstract: This is an observational retrospective study, which included 77 patients who underwent sacrospinous fixation (SSF) over a period of 3 years in a district general hospital. Casenotes were reviewed and all patients were invited to attend a further review appointment (14-49 months). The object was to determine short- and long-term success of SSF,particularly in elderly (28% were > or = 70 years), obese (24.7%) and medically compromised (64.9%) patients. Fifty-two patients (67.5%) had previous gynaecological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The most frequent complication is hemorrhage related to pudendal vascular injuries. Other complications include pudendal and sciatic nerve injuries, bladder injuries, gluteal pain, and suture abscess [7,24,25]. Pohl and Frattarelli found that bilateral SSLF resulted in increased blood loss of 25-50 mL and that the operative time was 20-30 minutes longer compared with unilateral SSLF [26].…”
Section: Clinical Outcomes and Complicationsmentioning
confidence: 99%
“…The most frequent complication is hemorrhage related to pudendal vascular injuries. Other complications include pudendal and sciatic nerve injuries, bladder injuries, gluteal pain, and suture abscess [7,24,25]. Pohl and Frattarelli found that bilateral SSLF resulted in increased blood loss of 25-50 mL and that the operative time was 20-30 minutes longer compared with unilateral SSLF [26].…”
Section: Clinical Outcomes and Complicationsmentioning
confidence: 99%
“…Some scholars opine that preventive apical vaginal reconstruction can be performed on patients who are at a high risk of apical vaginal prolapse after hysterectomy [ 4 , 22 ]. SSLF or USCLF can be selected for patients with degree III or IV uterine prolapse, where the apex of the vagina may prolapse to or beyond the vaginal orifice under traction after hysterectomy; SSLF is recommended if the uterosacral ligament is found to be apparently lax or weak and cannot be used as support during the surgery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%